The ribosomal L5 protein is associated with mdm-2 and mdm-2-p53 complexes. - Marechal, V (1994)
Throughout the purification of the mdm-2 or mdm-2-p53 protein complexes, a protein with a molecular weight of 34,000 was observed to copurify with these proteins. Several monoclonal antibodies directed against distinct epitopes in the mdm-2 or p53 protein coimmunoprecipitated this 34,000-molecular-weight protein, which did not react to p53 or mdm-2 polyclonal antisera in a Western immunoblot. The N-terminal amino acid sequence of this 34,000-molecular-weight protein demonstrated that the first 40 amino acids were identical to the ribosomal L5 protein, found in the large rRNA subunit and bound to 5S RNA. Partial peptide maps of the authentic L5 protein and the 34,000-molecular-weight protein were identical. mdm-2-L5 and mdm-2-L5-p53 complexes were shown to bind 5S RNA specifically, presumably through the known specificity of L5 protein for 5S RNA. In 5S RNA-L5-mdm-2-p53 ribonucleoprotein complexes, it was also possible to detect the 5.8S RNA which has been suggested to be covalently linked to a percentage of the p53 protein in a cell. These experiments have identified a unique ribonucleoprotein complex composed of 5S RNA, L5 protein, mdm-2 proteins, p53 protein, and possibly the 5.8S RNA. While the function of such a ribonucleoprotein complex is not yet clear, the identity of its component parts suggests a role for these proteins and RNA species in ribosomal biogenesis, ribosomal transport from the nucleus to the cytoplasm, or translational regulation in the cell.